La doctrina kantiana del esquematismo trascendental - Arias-Albisu, Martín (2005)
The paper’s purpose is to offer an interpretation of Kant’s Critique of Pure Reason’s chapter "On the schematism of the pure concepts of the understanding”. Our hypothesis is that in the doctrine of the schematism the possibility of the ontological constitution of the object as object is decided. Thus we will show that only with the transcendental schemes we find the basic ontological predicates of objectivity. This is demonstrated by establishing that only thanks to the doctrine of schematism the inner dynamism of the cooperation between sensibility and understanding gives place to objective knowledge.